2021
DOI: 10.1186/s12890-021-01466-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin (AAT) augmentation therapy in individuals with the PI*MZ genotype: a pro/con debate on a working hypothesis

Abstract: Alpha-1 antitrypsin deficiency (AATD) is a significantly under-diagnosed genetic condition caused by reduced levels and/or functionality of alpha-1 antitrypsin (AAT), predisposing individuals to lung, liver or other systemic diseases. The management of individuals with the PI*MZ genotype, characterized by mild or moderate AAT deficiency, is less clear than of those with the most common severe deficiency genotype (PI*ZZ). Recent genetic data suggest that the PI*MZ genotype may be significantly more prevalent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…28,29 More surprising is the indication of AT in almost 10% of cases with Pi*MZ genotypein this case, age <45 years, a DLCO (%) <50% and being symptomatic were the most relevant variables to decide the initiation of AT. It is of note that AT in Pi*MZ patients is off label, there is no evidence of efficacy of AT in Pi*MZ individuals 30,31 and, therefore, it is not recommended by guidelines. [7][8][9] Since the introduction of AT in the late 80s the same regimen of 60 mg/Kg weekly has been recommended for patients with severe AATD and lung disease based on biochemical efficacy restoring serum AAT levels above the protective threshold, 4,5 irrespective of the severity and phenotype of the respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 More surprising is the indication of AT in almost 10% of cases with Pi*MZ genotypein this case, age <45 years, a DLCO (%) <50% and being symptomatic were the most relevant variables to decide the initiation of AT. It is of note that AT in Pi*MZ patients is off label, there is no evidence of efficacy of AT in Pi*MZ individuals 30,31 and, therefore, it is not recommended by guidelines. [7][8][9] Since the introduction of AT in the late 80s the same regimen of 60 mg/Kg weekly has been recommended for patients with severe AATD and lung disease based on biochemical efficacy restoring serum AAT levels above the protective threshold, 4,5 irrespective of the severity and phenotype of the respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 More surprising is the indication of AT in almost 10% of cases with Pi*MZ genotypein this case, age <45 years, a DLCO (%) <50% and being symptomatic were the most relevant variables to decide the initiation of AT. It is of note that AT in Pi*MZ patients is off label, there is no evidence of efficacy of AT in Pi*MZ individuals 30 , 31 and, therefore, it is not recommended by guidelines. 7–9…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that among patients diagnosed with COPD the prevalence of the PiMZ genotype ranges from 1% to 22%. 1 , 27 , 42 According to these percentages of genetic penetrance, up to one-fifth of the estimated 35 million of the MZ carriers from the 74 selected countries (ie, approximately 7 million) will develop COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Really, the “threshold” value represents a systemic concentration of AAT in serum rather than its level in the alveolar fluid, and thus does not accurately reflect the AAT functional activity into the lungs. 42 Another factor that may play a significant role in the development of lung emphysema is the gene expression of neutrophil elastase that could be increased in MZs, contributing to aggravate the AATD protease/antiprotease imbalance. 42 Lately, it has been reported that several “rare/M-like and Z” compound heterozygotes, correctly characterized by gene sequencing, initially were misdiagnosed as PiMZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation